2011
DOI: 10.7205/milmed-d-10-00470
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Armor on Performance, Thermal Stress, and Exertion: A Critical Review

Abstract: Armed forces worldwide utilize some form of body armor as part of their personal protective system. This is particularly essential in recent times because of the increased sophistication of weapons employed during modern warfare and the advent of unconventional combat methods (such as the increased use of improvised explosive devices). There is some evidence to show, however, that the usage of military body armor impairs physical performance. This review of the literature will focus on the effect of body armor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Among the ergonomic problems, weight was regarded as the most important factor (Mclellan et al, 1998;Webster et al, 2005;Kim et al, 2011aKim et al, , 2011b. As consistently supported by researchers, weight carried by the body leads to impairment of human performance, with 2.4% to 3.5% performance decrement per kilogram (Larsen et al, 2011). McLellan et al (1998) reported that cooling advantage outweighs the augmentation of metabolic heat production induced by load carriage of the MCG until the cooling rate exceeds the metabolic rate.…”
Section: Practical Application In Industrial Settingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Among the ergonomic problems, weight was regarded as the most important factor (Mclellan et al, 1998;Webster et al, 2005;Kim et al, 2011aKim et al, , 2011b. As consistently supported by researchers, weight carried by the body leads to impairment of human performance, with 2.4% to 3.5% performance decrement per kilogram (Larsen et al, 2011). McLellan et al (1998) reported that cooling advantage outweighs the augmentation of metabolic heat production induced by load carriage of the MCG until the cooling rate exceeds the metabolic rate.…”
Section: Practical Application In Industrial Settingsmentioning
confidence: 96%
“…Ergonomic problems induced by MCGs, such as additional weight, layer, and body movement restriction, are inevitable (Kenny, et al, 2011). These problems may lead to excessive metabolic production and decreased heat dissipation, thereby aggregating body heat strain (Larsen, et al, 2011). Mobility and movement restriction problems may also induce physiological (e.g., musculoskeletal pain) and psychological discomfort (AkbarKhanzadeh, et al, 1995), thus leading to early fatigue or impaired human performance (Nunneley, 1989).…”
Section: Practical Application In Industrial Settingsmentioning
confidence: 98%
“…Although the adverse thermal effects of protective clothing in military settings have been well documented there is a scarcity of research that solely focuses on lightweight, non-military body armour (Larsen et al, 2011(Larsen et al, , 2012Stewart and Hunt, 2011;Stewart et al, 2013). To our knowledge this was the first study that examined these ensembles in a controlled laboratory setting.…”
Section: Discussionmentioning
confidence: 95%
“…high ambient temperature, high radiant heat, high humidity) (Budd, 2001;Sawka and Pandolf, 2002;Eglin et al, 2004;Cuddy and Ruby, 2011). In addition, significant increases in thermal strain have been demonstrated for numerous occupational ensembles relevant to firefighters and military personnel, including fully encapsulated hazard suits, body armour, and firefighting turnout equipment (Holmer et al, 1999;Rissanen et al, 2007;Caldwell et al, 2011;Larsen et al, 2011). Whilst energy cost or relative task intensity may not altered, thermal stress can diminish the capacity for personnel to perform work due to factors associated with elevated core body temperature (Montain and Coyle, 1992;Gonzalez-Alonso et al, 1999;Havenith, 1999;Barr et al, 2010).…”
Section: Climate and Thermal Strainmentioning
confidence: 96%